Rainfall Forecasting in Makassar City Using Triple Exponential Smoothing Method - Irwan Irwan; Muhammad Abdy; Ersa Karwingsi; Ansari Saleh Ahmar (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2023)
The purpose of this study is to determine the appropriate forecasting method for predicting rainfall in Makassar City in 2022. This research is based on the problems that are often experienced by the people of Makassar City, namely the occurrence of flooding which results in traffic jams due to high x rainfall which continuously occurs. for several days in a row. With this research, people can see the prediction of rainfall and anticipate flooding in Makassar City. The results of the Makassar city rainfall data plot experience increases and decreases (fluctuations), which tend to repeat every year. This shows that Makassar City's rainfall contains seasonal factors. Therefore the method used is one-parameter Brown triple exponential smoothing, three-parameter Holt-Winters additive and Holt-Winters multiplicative. The forecasting results show that the correct method to use is the Holt-Winters multiplicative method with a parameter value of a=0.001 β=0.15 γ=0.002 which produces a minimum value of MAPE = 1.18 MAD = 136.23 compared to the Brown and Holt-Winters methods additive. Forecasting results using the Holt-Winters multiplicative method show that the highest rainfall occurs from December to April 2022.